TikTok activism: Analisis aktivisme digital #TolakRUUTNI di platform TikTok - Cakrawala, Jenna Jelajah; Priyadharma, Subekti Wirabhuana; Rahmawan, Detta (Program Studi Ilmu Komunikasi UII, 2026)
The revision of the Indonesian National Armed Forces Bill (RUU TNI) has sparked a wave of public opposition, including through digital activism on the TikTok platform using the hashtag #TolakRUUTNI. This study used a qualitative approach with a netnography method through observation of 23 selected TikTok videos and user interactions in the comments section. The results show that digital activism through the hashtag #TolakRUUTNI is constructed into three main themes of criticism, namely criticism of the substance and legislative process, framing of the context of actors and history, and criticism of public apathy, accompanied by calls for solidarity. Criticism is conveyed through various digital communication strategies, namely citizen journalism, sarcasm, fear appeal, emotional expression, playful activism, and calls to action. This study contributes to the study of digital communication in understanding how TikTok is used as a space for conveying messages about social and political issues.